Pengaruh Organizational Culture Dan Work Environment Terhadap Job Performance Driver Grab Di Mediasi Job Satisfaction Di Kecamatan Cikarang Barat Kabupaten Bekasi - Naufal basyir; Retno Purwani Setyaningrum (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to examine the influence of Organizational Culture and Work Environment on the Job Performance of Grab driver-partners, with Job Satisfaction as a mediating variable. A quantitative approach with a causal- explanatory research design was employed, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0 software. A total of 100 respondents were selected using simple random sampling. The findings indicate that Organizational Culture has no significant effect on Job Satisfaction but has a negative and significant effect on Job Performance. In contrast, Work Environment has a positive and significant impact on both Job Satisfaction and Job Performance. Furthermore, Job Performance significantly influences Job Satisfaction and serves as a mediating variable in the relationship between both Organizational Culture and Work Environment on Job Satisfaction. These results offer important implications for human resource management in the digital transportation sector, particularly in enhancing the performance and satisfaction of Grab drivers.